GABAergic and nitriergic influence in antianxiety-like Activity of Garlic in Mice - Neeraj Gilhotra, Dinesh Dhingra (Journal of Applied Pharmaceutical Science, 2016)
Objectives: To investigate the GABAergic and nitriergic mechanism involved in the anxiolytic-like profile of ethanolic extract of garlic (GE).Materials and Methods: Male Swiss albino mice were employed in the present study. Stress was produced in mice by immobilizing them for 6h. Elevated plus maze, light/dark box and social interaction test were used for the assessment of anxiety in mice. Concentrations of GABA in brain and nitrite level in plasma were estimated to determine the possible involvement of GABAergic and nitriergic mechanisms in the anxiolytic profile of GE.Results: The present study showed that the GE produced significant antianxiety- like activity in unstressed and stressed mice. In unstressed mice, GE significantly increased GABA levels, but could not produce any change in nitrite levels. Meanwhile, in stressed mice, GE significantly increased GABA levels along with a significant decrease in nitrite levels. Pre-treatment with aminoguanidine, an inducible nitric oxide synthase inhibitor, significantly enhanced the anxiolytic-like activity of GE, as compared to GE and aminoguanidine alone in stressed mice, but not in unstressed mice. On the other hand, pretreatment with 7-nitroindazole, a neuronal nitric oxide synthase inhibitor, did not produce any significant change in antianxiety- like activity of GE in unstressed as well as stressed mice.Conclusion: It has been concluded that the garlic may possess anxiolytic- like activity and possess NOS inhibiting property in stressed mice, which may add to its status to be used in stress-induced anxiety conditions.
Keywords: Aminoguanidine, anxiety, GABA, garlic, nitric oxide.